Effect of Earnings Management, Liquidity Ratio, Solvency Ratio and Ratio Profitability of Bond Ratings in Manufacturing: (Case Study Sub-Sector Property and Real Estate Sector Companies listed on the Indonesia Stock Exchange (IDX)) - Syarifah Syarifah (Research Collaboration Community (RCC), 2021)
This study aims to analyze the effect of earnings management, liquidity ratios, solvency ratios, and profitability ratios on bond ratings. The population of this study is 45 companies listed on the Indonesia Stock Exchange in the property and real estate sector during the 2017-2020 period,by processing data using Eviews Version 9. The sampling technique used was purposive sampling method and 4 companies were selected as samples. This study uses quantitative descriptive methods and multiple regression tests to determine the relationship between variables. Based on the results of the study prove that earnings management, liquidity ratios, solvency ratios, and profitability ratios have an effect on simultaneously on bond ratings. earnings management partially has a negative effect on bond ratings, liquidity ratio partially has a positive and significant on bond ratings, solvency ratio and profitability ratio partially has negative on bond ratings. The obligations of a property and real estate sector company given by a depository are important for investors to know because investors will know the rating of the company that is eligible or not to invest.